China encircled - Enkhbat, Narantsatsral (Kansas State University, 2021)
China is a country with unique geographic position surrounded by twenty nations big and small (including Taiwan) around its periphery. China`s greatest security concern has always been a strategic encirclement – its neighbors aligning with one another or with strong powers such as the United States to isolate China. How does this sense of encirclement influence China’s strategic behavior? Can China’s resort to military force be linked to the fear of encirclement? This study develops the theory of strategic encirclement. When nations encounter an increasing nonmilitary and military involvement by other powers around their periphery, they have options of various kinds of strategies to mitigate such threats. The states have choices of carrots and sticks to either punish or to provide positive incentives to convince periphery states not to align with hostile great powers. This study argues that under certain conditions, non-coercive approaches to deal with strategic encirclement are improbable. This research offers underlying and proximate conditions under which an encirclement leads to an interstate conflict. Military encirclement is an underlying condition that paves the way for an interstate conflict while the strategically important geographic area, threats of two-front conflicts and the national leadership`s mobilization intent are considered as proximate conditions. Major arguments about China`s conflict behavior basically agree upon the notion that China’s use of force often involved issues of Chinese sovereignty and territorial integrity. In other words, China opted for military force when its border security was threatened, or its territorial integrity or sovereignty was challenged. This thesis has challenged this major argument, suggesting that China has employed military force externally mostly for greater strategic reasons – beyond the mere defense of its borders – avoiding strategic encirclements by the strong powers. This study, examining four cases on China`s external conflicts since 1949, concluded that central to Chinese calculation to use force was securing its strategic position to avoid being encircled by its adversaries.
Keywords: Encirclement; Conflict; Security; Military strategyChina